Peripherally administrated prions reach the brain at sub‐infectious quantities in experimental hamsters. Issue 5 (1st February 2014) - Chen, Baian; Soto, Claudio; Morales, Rodrigo
Abstract : The mechanisms implicated in prion infection and tissue distribution are not completely understood. In this study we investigated the levels of 263K prions in brain and spleen of Syrian hamsters few days after intra‐peritoneal challenge. For this purpose we utilized the PMCA technology which permits to detect as little as few PrP Sc molecules. Our results show that peripherally administered prions directly reach the brain, although at levels below the minimum necessary to produce disease. PrP Sc remains in the brain several days after administration suggesting inefficient clearance or early replication. Understanding the fate of the infectious agent after administration and its uptake in different organs and fluids may provide useful information to develop strategies to minimize further spreading of prion diseases. Abstract : We identified sub‐infectious presence of prions in brains and spleens after peripheral administration. We report the persistence of this material for up to 9 days after challenge in both, spleen and brain. We describe a new methodology to detect infectious prions in tissues at early stages of in vivo replication.